Multiwavelength Observations of 6 FSRQ in 2008–2012. Issue Volume 9:Issue S304(2013) (25th July 2014) - Troitskiy, I. S.; Morozova, D. A.; Jorstad, S. G.; Larionov, V. M.; Marscher, A. P.; Agudo, I.; Blinov, D. A.; Smith, P. S.
Abstract: We present results of 4 years of VLBA monitoring along with γ-ray and optical R-band photometric observations of 6 blazars (0420-014, 1156+295, 1222+216, PKS 1510-089, 1633+382 and CTA 102). We have analyzed total intensity images obtained with the VLBA at 43 GHz and investigated kinematic evolution of the pc-scale jets of the sources. For all sources we compare flux variations in the VLBI core and bright superluminal knots with γ-ray and optical light curves. The majority of γ-ray flares are coincident with the appearance of a new superluminal knot and/or a flare in the millimeter-wave core and at optical wavelengths. These results support the conclusion that for many flares in blazars the region of the enhanced γ-ray and optical emission is located in the vicinity or downstream of the mm-wave VLBI core.